La geosinonímia dels ceps i raïms catalans - Favà i Agud, Xavier (Caplletra. Revista Internacional de Filologia, 1999)
This paper deals with a number of geosynonyms within grapes and wine terminology in Catalan; twenty-nine names of vines and grapes (technically called «ampelonyms») are analyzed: «boval, garnatxa, giró, pansal, palop, monastrell, picapoll or moscatell», amongst others. The author, aware of the lack of dialectal maps concerning specific terminology, has drawn nine maps of these ampelonyms, based on extensive fieldwork, with surveys he has carried out in all Catalan-speaking areas. The paper is supplemented by numerous bibliographical references and complementary information (often infootnotes) on the names of the grapes studied: etymological hypotheses, parallelisms in other Romance languages, etc.